MARKETING STRATEGY FOR MSME HEALTH BEVERAGE PRODUCTS - Sri Sahbany; Irawansyah Irawansyah; Detty Agustin Riscal; Baiq Isti Hijriani; Jumari Ustiawaty; Andi Muhammad Aminullah; Nurul Khatimah Ismatullah; Adriyan Suhada (Jurnal Pengabdian Masyarakat Sehati, 2023)
In Indonesia, you often find drinks labeled "healthy drinks" which are commonly consumed by the public, but the process of making healthy drinks takes quite a lot of time and effort so it's not wrong, especially as the best-selling position is added by ready-to-drink drinks with contemporary flavor variants. Therefore, to overcome this problem, a new innovation was carried out by producing health drinks using local ingredients. The problem formulation taken is how to market health drinks. For this reason, the aim of the service regarding the marketing of health drinks is expected to be a breakthrough in making people aware to choose health drinks more wisely. The location of this service activity is in Bagikpolak Village, Labuapi District, West Lombok Regency. Socialization activities regarding the socialization of health drink marketing strategies have been carried out using lecture, discussion and question and answer methods. In general, this service activity ran smoothly. Based on this, the conclusion that can be drawn is that participants in service activities know beverage marketing strategies wisely, rationally and appropriately to convey to other communities.